The Feasibility Study of Utilising Electronic Nose and ANN for Plant Malaise Detection - Marni Azira, Markom; Ali Yeon, Md Shakaff, Prof. Dr.; Abdul Hamid, Adom, Assoc. Prof. Dr.; Mohd Noor, Ahmad, Prof. Dr.; Abu Hassan, Abdullah (Universiti Malaysia Perlis (UniMAP), 2008)
Organized by Universiti Malaysia Perlis (UniMAP), 15th - 16th March 2008 at Putra Brasmana Hotel, Perlis.